E-Sports and Sports: A Study of the Related Position of E-Sports in Sports - Ikadarny Ikadarny; Muhammad Qasash Hasyim; Sufitriyono Sufitriyono; Suparman Suparman (Universitas Majalengka, 2023)
Although many studies have concluded that E-Sports are sports, the question of whether they should be classified as a sport continues. This is the basis for researchers to write articles by utilising the literature review process. This strategy was chosen because there are still many assumptions that E-Sports is a profit-oriented gaming activity. Recent articles provide evidence that the definition of e-Sports is more than just playing games for money. In addition, the perception of E-Sports is also limited to video games, even though the essence of E-Sports is more than that. It is undeniable that E-Sports are directly related to the economy, but the study of E-Sports is not only seen from one side; other aspects that can make E-Sports recognised as a sport are reviewed in this article. This article concludes that E-Sports can be classified as a sport by using the values and features of the sport. Such as being competitive, having rules, doing physical activity, practising according to the coach's programme, paying attention to player nutrition, and the professionalism of players in running the game.